Evaluation of a new continuous mononuclear cell collection procedure in a single transplant center cohort enriched for AL amyloidosis patients. Issue 3 (June 2018) - Pudusseri, Anita; Smith, India; Sarnacki, Diane; Brauneis, Dina; Shelton, Anthony; Sanchorawala, Vaishali; Sloan, J. Mark; Sarosiek, Shayna; Quillen, Karen
Abstract: Background: The Spectra Optia continuous mononuclear cell (CMNC) program is newly available, and herein validated in a single-center cohort enriched with AL amyloidosis patients to collect a target CD34+ yield of 2.5 × 10 6 cells/kg within 2 days. Methods: Consecutive autologous transplant patients in 2016 are included. Patients undergo leukapheresis with Optia CMNC and Spectra v4.7 over a 2-day cycle. Data collection includes collection efficiency, adverse events and engraftment kinetics. Results: 36 leukapheresis procedures on 18 patients are included. The diagnoses are AL amyloidosis (9), myeloma (7), lymphoma (2), and scleroderma (1). Median age is 60; 12 are men. Plerixafor was employed pre-emptively in 6 cycles. Median blood CD34+ on Day 1 of leukapheresis was 46 cells/uL. Median number of blood volumes processed on Day 1 was 3.1. All collection cycles were completed within 2 days; only one in a heavily pretreated lymphoma patient did not reach the target requiring a second mobilization attempt. Mean collection efficiencies were comparable between the two devices. There were 2 adverse events: tubing rupture on the Optia; and one case of hypotension. All 18 patients underwent high-dose chemotherapy: median cell dose infused was 7.7 × 10 6 CD34+ cells/kg. Median days to neutrophil and platelet engraftment were 10 and 13 respectively. Conclusion: The Optia CMNC collection protocol is safe and effective in a small single-center autologous stem cell transplant cohort enriched for high-risk patients with AL amyloidosis and cardiac involvement. Caution is needed for tubing setup because there is less cumulative experience with Optia.